2007
DOI: 10.1007/s00256-007-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic evaluation of calcaneal fractures: to measure or not to measure

Abstract: Objective The aim of this study was to correlate the functional outcome after treatment for displaced intraarticular calcaneal fracture with plain radiography. Design The design was a prognostic study of a retrospective cohort with concurrent follow-up. Patients A total of 33 patients with a unilateral calcaneal fracture and a minimum follow-up of 13 months participated. Patients filled in three disease-specific questionnaires, graded their satisfaction and the indication for an arthrodesis was noted. Standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 42 publications
4
50
0
7
Order By: Relevance
“…Functional outcome, as measured using patient-reported outcome measures, was not used. Previous research showed that measurements on plain radiographs were not useful in determining outcome after intra-articular calcaneal fractures [22]. However, they are useful for determining fracture healing, alignment and surgical restoration of anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Functional outcome, as measured using patient-reported outcome measures, was not used. Previous research showed that measurements on plain radiographs were not useful in determining outcome after intra-articular calcaneal fractures [22]. However, they are useful for determining fracture healing, alignment and surgical restoration of anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subtalar joint frequently collapses (calcaneal collapse) post-operatively to some extent, which can be seen at radiological follow-up [11,14,24]. Several authors noted a correlation between initial BA and outcome [3,10,15,18,22,24]. The BA at time of admission appears to be a valuable prognosticator for functional longterm results [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also as reported by Sanders, Crosby and Fitzgibbons classified fractures as nondisplaced, displaced or comminuted; Sanders further classified fractures according to the number and location of posterior facet articular fragments on CT [4]. There is little evidence that these classification systems can be applied reliably [5], let alone point to biologically distinct entities, although there is evidence that with the Sanders' classification, higher types correlate with worse prognosis.…”
Section: Injury Considerationsmentioning
confidence: 97%
“…го лечения выполняли: рентгенографию обоих голеностопных суставов в двух стандартных про-екциях и в боковой проекции в положении стоя с нагрузкой для определения угла между лини-ями, проведенными вдоль оси большеберцовой кости и оси шейки таранной кости (бокового та-ранно-большеберцового угла) [19,22]. Также про-водили рентген-функциональное исследование в боковой проекции, что позволяло оценить сум-марную подвижность суставов среднего отдела стопы в сагиттальной плоскости при максималь-ном тыльном и подошвенном сгибании (опреде-ляли углы между осью таранной кости и длинной осью первой плюсневой кости в крайних точках движения).…”
Section: материал и методыunclassified